Employ Your Mind (EYM), a vocational rehabilitation and cognitive remediation program: the participants’ experience - Pruscino, Ilona; Pope, Kirsty; Khan Willoughby, Khalsom; Miles, Anne (Frontiers in Psychiatry, 2025)
BackgroundThe experience of cognitive challenges due to mental health conditions can significantly affect a person’s level of functioning and recovery including engagement in employment and other vocational pursuits. Cognitive remediation is an evidence-based treatment that has been demonstrated to improve cognitive and functional outcomes when embedded within a psychosocial rehabilitation program. Facilitated by occupational therapists, often with co-facilitators who are mental health workers and/or peer workers, Employ Your Mind is a vocational rehabilitation program incorporating cognitive remediation. To date the lived experience of Employ Your Mind has not been examined. This qualitative study aimed to explore the participant’s perspective of the value of the Employ Your Mind program.MethodsSemi-structured in-depth interviews were conducted with purposively sampled participants. The qualitative data was transcribed verbatim prior to undergoing thematic analysis. The utilisation of member checking and researcher reflexivity augmented the trustworthiness of this study.ResultsFindings from participants (n=4) highlights the requirement for a ‘just-right challenge’, heightens the value of the therapeutic relationship and reinforces the advantages of flexible service provision to harness participant motivation and promote optimal outcomes.DiscussionThis study reinforces the necessity of obtaining the lived experiences of participants to shape the evolution of cognitive remediation, particularly in the field of vocational rehabilitation, by providing a qualitative voice to enhance program delivery.